Application of Vascular grafts od Polyvinyl alcohol hydrogel associated to mesenchymal stem cells from whartons jelly in an animal model. - Alexandre, Nuno (2013)
Application of vascular grafts of the polyvinyl alcohol hydrogel (PVA) associated with MSCs from Wharton jelly in an animal model (sheep). N Alexandre, MA Lopes, N Fernandes, M Rodrigues, I Amorim, AC Mauricio, AL Luís Introduction: There is a great demand for new artificial vascular grafts of small diameter (< 6 mm) due to the functional limitations of the currently used biomaterials (ePTFE and Dacron). Polyvinyl alcohol hydrogel (PVA) is a biomaterial that has been used for several biomedical applications in the past and more recently as a vascular graft. Although, the use of PVA as a vascular graft was never been tried in experimental and clinical settings with the exception of a small study using rats. In order to reduce the thrombogenicity of the lumen of PVA vascular grafts, an anticoagulant, dextran, was used in the production of these grafts. Mesenchymal stem cells (MSCs) form Wharton’s jelly are easy to isolate and expand and have been demonstrated capable of differentiating into various cell lineages. In this work, MSCs from Wharton’s jelly of human umbilical cord were used, associated with a PVA vascular grafts to improve their biointegration. Methods: PVA vascular grafts were prepared by the freeze/thawing technique and made with 5 cm of length and an internal diameter of 5 mm. The graft wall thickness was inferior to 1 mm. Six sheep were anesthetized and a surgical access to the left common carotid artery was made. A segment of the carotid was removed and end-to-end anastomosis was made with the PVA graft using 6/0 USP polypropylene suture. Non-differentiated human stem cells (MSCs) were isolated from Wharton’s jelly of umbilical cord and multiplied in vitro and placed into syringes for a total volume of 1 ml with an average concentration of 1 x 106 cells/ml and were injected perivascularly. Following the surgery was instituted a protocol with anticoagulants (clopidogrel, warfarin and heparin) with the objective of reducing prosthesis trombosis.The functional performance of the prosthesis was evaluated by vascular ultrasound in Doppler and B mode by measuring parameters such as: peak systolic/diastolic blood flow velocity, vascular diameters at implantation and at the periphery. These measurements are performed at various time points of the experiment and were followed by euthanasia of sheep and immediately sample collection was performed for the implementation of techniques like immunohistochemistry, morphometry and scanning electronic microscopy Results and Discussion: In the present work the PVA prosthesis of presented a patency rate of 100% at 24 hours. At 4 weeks the patency rate lowered for 50% and for 40% at 8 weeks post-surgery. 12 weeks post-surgery the patency rate decreased further to 25%. During the 12 weeks period, none of the animals presented signs of infection and adhesions at implant site. Functional evaluation showed that the cause of obstruction was thrombosis at implant - carotid artery transition. The patency rate of PVA grafts was similar to other biomaterials in experimental settings and the prevalence of thrombosis is higher at the 48 hours post-surgery as expected. Comparing PVA to other grafts (PTFE and Dacron) currently used in human patients, the patency rate was lower; however sheep is considered a hipercoagulable specie’s with a higher level of fibrinogen predisposing to thrombosis at anastomosis locations. No implant dilation or rupture was observed in vivo which supports the biomechanical properties observed in vitro has been published. Conclusions:In the present work was possible to demonstrated that PVA can be used as a functional vascular prosthesis that can support long term patency of blood flow in a hipercoagulable specie´s.